A Creative Approach to Creating Children's Dance: Fan Dance at Sanggar Galatiak Pitameh, Padang City - Adinda Rahmasari Putri; Darmawati (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
This research aims to describe the Creative Approach to Creating Children's Dance: Fan Dance at the Galatiak Pitameh Studio, Padang City. This type of research uses a descriptive method of qualitative research. The object of his research is the Fan dance at the Galatiak Pitameh studio in the city of Padang and is focused on a creative approach to its creation. Data collection techniques are library techniques, observation, interviews, and documentation. The results showed that the creative approach to creating the Sanggar Galatiak Pitameh Fan dance has three stages, (1) The exploration stage, namely the stage that has a sense of sensitivity to objects, by listening to music that has been chosen as accompaniment to the Fan dance. (2) The improvisation stage, namely the power of imagination and thinking power to concentrate on objects, in broader improvisation develops the power of imagination that has been obtained in the exploration process. Carrying out spontaneous movements that arise from self-awareness, using free movements in using a fan as a property, by showing happy facial expressions. At this stage, the results of the search for motion are directly practiced by the dancers, but in the process, the little dancers also have creative power. Of them have a spontaneous response to the motion given so that it is more varied in nature. (3) Formation stage, that is, the climax process of the formation stage which means it has been completed, changing the form of movement from the previous stages, then trying to form the movement into a complete dance movement.